Extinction vulnerability of coral reef fishes - Graham, Nicholas A.J; Chabanet, Pascale; Evans, Richard D; Jennings, Simon; Letourneur, Yves; Aaron MacNeil, M; McClanahan, Tim R; Öhman, Marcus C; Polunin, Nicholas V.C; Wilson, Shaun K (Ecology letters, 2011)
Ecology Letters (2011) 14: 341-348 ABSTRACT: With rapidly increasing rates of contemporary extinction, predicting extinction vulnerability and identifying how multiple stressors drive non-random species loss have become key challenges in ecology. These assessments are crucial for avoiding the loss of key functional groups that sustain ecosystem processes and services. We developed a novel predictive framework of species extinction vulnerability and applied it to coral reef fishes. Although relatively few coral reef fishes are at risk of global extinction from climate disturbances, a negative convex relationship between fish species locally vulnerable to climate change vs. fisheries exploitation indicates that the entire community is vulnerable on the many reefs where both stressors co-occur. Fishes involved in maintaining key ecosystem functions are more at risk from fishing than climate disturbances. This finding is encouraging as local and regional commitment to fisheries management action can maintain reef ecosystem functions pending progress towards the more complex global problem of stabilizing the climate.